Acid reactions in hub systems consisting of separate non-reactive CO2 transport lines. (August 2019) - Morland, Bjørn H.; Tjelta, Morten; Norby, Truls; Svenningsen, Gaute
Highlights: Acid are produced with low ppmv level of impurities (SO2, NO2, and H2 S) in dense phase CO2 at 25 °C and 100 bar. At 10 ppmv of SO2, NO2, and H2 S, chemical reactions occurred but these was not regarded as harmful. No condensed acid was detected. The solubility of the acids determine the allowed impurity concentration limit, and the limit could be between 10 and 35 ppmv of SO2, NO2, and H2 S. NO2 might act as a catalyser and as long O2 is present, the chemical reaction would continue. Abstract: Corrosion in carbon steel pipelines is a major threat for safe CO2 transport, and there have been several projects studying the corrosivity of impurities which could be found in captured CO2 . Often only two or three of these impurities have been present while performing the experiments. Although these experiments have delivered valuable knowledge, there are still questions of what happens when impurities are present together. Furthermore, several transport pipelines may deliver CO2 to a main pipeline through a hub system for storage or utilization, and while these streams may be safe individually, the blend in the main pipeline could create components that are hazardous for carbon steel. The present study used a novel experimental setup to realistically simulate a CO2 hub. Three individual "pipelines" were joined inside a glass tube in a transparent autoclave. The three "pipelines" were connected to three different reservoir pumps, simulating different capturing sources with dissimilar types of impurities. This gave a mix of low (ppmv) levels of oxygen (O2 ), sulphur dioxide (SO2 ), hydrogen sulphide (H2 S), nitrogen dioxide (NO2 ), and water (H2 O). Three different experiments were performed with concentrations ranging from 5 to 35 ppmv of the impurities and a total pressure of 100 bar at 25 °C. All impurities were measured before and after the streams were mixed in the autoclave. The experiments revealed that reactions between certain species occured even at concentrations as low as 5 ppmv, but the reaction products were not considered detrimental in terms of corrosion. If the impurity concentrations were increased to about 35 ppmv, acids and solids were produced, and the situation became unacceptable for carbon steel.